Effectiveness of visual inspection of Acetic Acid (VIA) and Pap Smear in cervical cancer screening: Literature review - Mastina, Mastina; Sari, Ana Puspita; Lestrari, Siti (Universitas 'Aisyiyah Yogyakarta, 2023)
Cervical cancer is the second most common cancer among women worldwide, with an estimated 528,000 cases and 260,000 deaths yearly (Kagabu et al., 2020). The incidence of cervical cancer in Indonesia in 2018 was 23.4 per 100,000, with an average death rate of 13.9 per 100,000 (Profil RI, 2020). This study aimed to compare the effectiveness of VIA and Pup Smear examinations. The research method uses literature, which involves reviewing and critically evaluating existing literature sources. Review of journals in this study by searching for journals in the database (Google Scholar and PubMed). The results of the study state that the sensitivity value of Pap smear is 97.14%. This shows that it is higher than the sensitivity of VIA examination, and the specificity value of VIA is higher at 94.5% compared to the specificity value of VIA. Of the two methods, Pap Smear Visual Inspection screening is more effective than VIA. This study concludes that the Pap Smear Visual Inspection screening method is more effective than the IVA method. The sensitivity and discipline for detecting high-grade scrotal intraepithelial lesions (HSIL) and squamous cell carcinoma (SCC) are higher than a pap smear.